Restriction of cytosolic sucrose hydrolysis profoundly alters development, metabolism, and gene expression in Arabidopsis roots. (30th December 2020) - Pignocchi, Cristina; Ivakov, Alexander; Feil, Regina; Trick, Martin; Pike, Marilyn; Wang, Trevor L; Lunn, John E; Smith, Alison M
Abstract : A reduction in cytosolic invertase in Arabidopsis roots changes the sucrose to hexose ratio, resulting in profound alterations of metabolism, growth, development, and patterns of gene expression. Abstract: Plant roots depend on sucrose imported from leaves as the substrate for metabolism and growth. Sucrose and hexoses derived from it are also signalling molecules that modulate growth and development, but the importance for signalling of endogenous changes in sugar levels is poorly understood. We report that reduced activity of cytosolic invertase, which converts sucrose to hexoses, leads to pronounced metabolic, growth, and developmental defects in roots of Arabidopsis ( Arabidopsis thaliana ) seedlings. In addition to altered sugar and downstream metabolite levels, roots of cinv1 cinv2 mutants have reduced elongation rates, cell and meristem size, abnormal meristematic cell division patterns, and altered expression of thousands of genes of diverse functions. Provision of exogenous glucose to mutant roots repairs relatively few of the defects. The extensive transcriptional differences between mutant and wild-type roots have hallmarks of both high sucrose and low hexose signalling. We conclude that the mutant phenotype reflects both low carbon availability for metabolism and growth and complex sugar signals derived from elevated sucrose and depressed hexose levels in the cytosol of mutant roots. Such reciprocal changes in endogenous sucrose and hexose levels potentially provide rich information about sugar status that translates into flexible adjustments of growth and development.